WILL CO-MANAGEMENT APPROACH BRING A GOOD PROSPECT FOR BABON RIVER MANAGEMENT IN SEMARANG, CENTRAL JAVA-INDONESIA? - Indah Susilowati (JOURNAL OF COASTAL DEVELOPMENT, 2002)
Semarang Municipality is passed by Babon river in the Eastern part. This river  flows from Ungaran in Semarang Regency at the upper-stream  and  streams down to Java sea  in Demak Regency.This river is utilised by various parties for multi-purposes. Thus, to manage Babon river and its watershed need coordination among the stakeholders. In this case, community as one of the competent stakeholders  is considered as the most important  role player who determine the success of sustainable river management. Babon river passes Semarang City longer than Semarang and Demak regencies. It seems  when the stakeholders  of Semarang pay more attention to Babon river will harvest more benefits compared to its costs. It  indeed needs  sharing in responsibility and understanding among the stakeholders along the watershed of Babon river. Collaborations between G to G (such as Germany and Indonesia) and Local Government (LG) to  LG are seriously needed to support the success of the river management. Nevertheless, many efforts have been made  on  it. As mentioned by Lilin (2000), the existing participation contributed by  community and key-persons along the Babon watershed in Semarang City were relatively low. The preliminary survey indicated that introducing co-management approach among the stakeholders  in managing Babon river will  provide  a good prospect in the future. Many evidences have shown the success of  co-management approach in managing natural resources in the third world countries in Asia, Africa and the developed ones. Babon river is a common resource, open-access to any parties and transboundary along three regions, thereby, need  protocol concept  to achieve the optimal  management. What are the priority and how co-management should be implemented in  Babon river are not easy questions but subject to further research.